Retraction: Block Adjustment of Large-scale Domestic Optical Satellite Remote Sensing Imagery without GCP in Antarctic (IOP Conf. Ser.: Earth Environ. Sci.428 012082). Issue 1 (January 2020) - Wang, Yi; He, Mingyuan; Xiang, Jie; Ge, Jingjing
Abstract : This article has been retracted by IOP Publishing. IOP Publishing was notified by the corresponding author that the corresponding author had breached the terms of our Publishing Licence and this article should not have been submitted and published. This is in violation of the IOP Publishing Licence. IOP Publishing therefore retracts this paper based on breach of the terms of the Licence. Retraction published: 23 February 2021